THE RISK FACTORS OF LEPROSY INDICENCE IN PIDIE JAYA REGENCY, ACEH, INDONESIA - Farrah Fahdhienie; Sitepu, Frans Yosep; Hamisah, Irma (Malaysian Journal of Public Health Medicine, 2026)
Leprosy is a contagious infectious disease that still causes high morbidity and mortality rates in the world. Uncontrolled risk factors can increase the transmission and cause permanent damage to nerves and human body tissue. The aim of the study was to determine the risk factors of leprosy. The study used a case control design with 42 respondents consisting of 12 leprosy cases and 24 neighbors of cases who did not have leprosy (1:2). Cases were patients confirmed bacteriologically at the community health center. Multivariate analysis by logistic regression was carried out to determine the most risk factors of the incidence of leprosy, using the P-Value < 0.05 and Odds Ratio (OR). People who had close contact (P-Value= 0.035; OR= 10.8; 95%CI= 1.07-108.62), did not get BCG vaccination (P-Value= 0.023; OR= 5.67; 95%CI= 1.28-25.02), low monthly income (P-Value= 0.031; OR= 9.75; 95%CI= 1.12-85.16), poor water resources (P-Value= 0.036; OR= 8.41; 95%CI= 0.96-73.73), and low level of knowledge (P-Value= 0.009; OR= 6.60; 95%CI= 1.48-29.36) were related to the incidence of leprosy. The most risk factors of the leprosy are did not get BCG vaccination (P-Value= 0.015; OR= 45.81; 95%CI= 2.08-10.96) and low level of knowledge (P-Value= 0.029;OR= 25.64; 95%CI= 1.39-473.13). People who did not receive BCG vaccination and had low knowledge were the main risk factors of leprosy in Pidie Jaya Regency. Close contact with leprosy patients and poor water sources also increased the risk through prolonged exposure and poor hygiene. Strengthening BCG coverage and public education is recommended